Failure of glucose to elicit a normal secretory response in fetal pancreatic beta cells results from glucose insensitivity of the ATP-regulated K+ channels. - Rorsman, P; Arkhammar, P; Bokvist, K; Hellerström, C; Nilsson, T; Welsh, M; Welsh, N; Berggren, P (1989)
Fetal pancreatic beta cells demonstrate a deficient insulin release in response to glucose, but the underlying mechanism at the cellular level is unknown. By using beta cells from 21-day fetal rats we made an attempt to clarify the mechanism(s) behind this reduced glucose response. In addition to measuring insulin release, glucose metabolism, and cellular ATP content, ATP-regulated K+ channels (G channels) and voltage-activated Ca2+ currents were investigated with the patch-clamp technique. It was thus demonstrated that the ATP-regulated K+ channels in fetal beta cells were not sensitive to glucose but otherwise had similar characteristics as those of adult beta cells. Also, the characteristics of the voltage-activated Ca2+ currents were similar in adult and fetal beta cells. However, as judged from measurements of both glucose oxidation and glucose utilization, glucose metabolism was impaired in fetal beta cells. In addition, there was no increase in the ATP content, even when the cells were stimulated for 30 min. It is therefore concluded that the attenuated glucose-induced insulin release in fetal pancreatic beta cells is due to an immature glucose metabolism resulting in impaired regulation of the ATP-sensitive K+ channels. These findings may be relevant to the understanding of the deficient stimulus-secretion coupling associated with non-insulin-dependent diabetes.